History and Prospects for the Application of X-Ray Diffraction Analysis in Seed Breeding and Seed Study - F. B. Musaev; S. L. Beletskiy (Известия высших учебных заведений России: Радиоэлектроника, 2021)
Introduction. X-ray analysis has been applied for visualizing the internal structure of various objects for over 100 years. However, this method began to be used for assessing the quality of plant seeds only in the early 1980s. The main impediment was a lack of specialized instruments, particularly X-ray sources, that could provide informative images. Advancements in the field of microfocus radiography allowed significant results to be achieved, including the preparation of the National Standard GOST R 596032021 "Agricultural Seeds. Methods of digital radiography".Aim. An analytical review of Russian research studies in the field of X-ray diffraction analysis of plant seeds.Materials and methods. Key stages in the development of microfocus X-ray diffraction analysis of seeds and individual parts of plants for agricultural and other purposes are considered. The design of instruments, including digital ones, created for the implementation of the method are described.Results. In order to obtain informative X-ray diffraction images of plant seeds, which objects are generally characterized by small sizes and small density, the focal spot of the X-ray tube should not exceed several tens of microns under the voltage of not higher than several tens of kilovolts. As a system for visualizing a latent X-ray image, it is preferable to use image receivers based on a screen with a photostimulated phosphor or flat-panel solid-state X-ray detectors. These instruments have been successfully used to identify and describe the radiographic signs of a normal seed and nine main types of defects for 600 plant species.Conclusion. In comparison with the conventional contact radiography, microfocus radiography produces X-ray images of seeds with a projection magnification of the image up to several tens of times. Such images permit highly detailed visualization of the structure of seeds that differ slightly in density.